Association between gut microbiota and Hirschsprung disease: a bidirectional two-sample Mendelian randomization study - Liu, Wei; Yan, Hanlei; Jia, Wanying; Huang, Jingjing; Fu, Zihao; Xu, Wenyao; Yu, Hui; Yang, Weili; Pan, Weikang; Zheng, Baijun; Liu, Yong; Chen, Xinlin; et al. (Frontiers in Microbiology, 2024)
Background Several studies have pointed to the critical role of gut microbiota (GM) and their metabolites in Hirschsprung disease (HSCR) pathogenesis. However, the detailed causal relationship between GM and HSCR remains unknown. Methods In this study, we used two-sample Mendelian randomization (MR) analysis to investigate the causal relationship between GM and HSCR, based on the MiBioGen Consortium’s genome-wide association study (GWAS) and the GWAS Catalog’s HSCR data. Reverse MR analysis was performed subsequently, and the sensitivity analysis, Cochran’s Q-test, MR pleiotropy residual sum, outlier (MR-PRESSO), and the MR-Egger intercept were used to analyze heterogeneity or horizontal pleiotropy. 16S rDNA sequencing and targeted mass spectrometry were developed for initial validation. Results In the forward MR analysis, inverse-variance weighted (IVW) estimates suggested that Eggerthella (OR: 2.66, 95%CI: 1.23–5.74, p = 0.01) was a risk factor for HSCR, while Peptococcus (OR: 0.37, 95%CI: 0.18–0.73, p = 0.004), Ruminococcus2 (OR: 0.32, 95%CI: 0.11–0.91, p = 0.03), Clostridiaceae1 (OR: 0.22, 95%CI: 0.06–0.78, p = 0.02), Mollicutes RF9 (OR: 0.27, 95%CI: 0.09–0.8, p = 0.02), Ruminococcaceae (OR: 0.16, 95%CI: 0.04–0.66, p = 0.01), and Paraprevotella (OR: 0.45, 95%CI: 0.21–0.98, p = 0.04) were protective factors for HSCR, which had no heterogeneity or horizontal pleiotropy. However, reverse MR analysis showed that HSCR (OR: 1.02, 95%CI: 1–1.03, p = 0.049) is the risk factor for Eggerthella. Furthermore, some of the above microbiota and short-chain fatty acids (SCFAs) were altered in HSCR, showing a correlation. Conclusion Our analysis established the relationship between specific GM and HSCR, identifying specific bacteria as protective or risk factors. Significant microbiota and SCFAs were altered in HSCR, underlining the importance of further study and providing new insights into the pathogenesis and treatment.